Integral metabolic indices as markers of increased arterial stiffness in young and middle-aged individuals with hypertension and other cardiovascular risk factors - V. I. Podzolkov; A. E. Bragina; N. A. Druzhinina; Yu. N. Rodionova; T. A. Safronova; R. A. Shikhmagomedov; K. K. Novikov (Кардиоваскулярная терапия и профилактика)
Aim. To study the relationship of integral metabolic indices with the Cardio-Ankle Vascular Index (CAVI) and assess their predictive value for identifying increased levels of arterial stiffness in young and middle-aged people with hypertension and other cardiovascular risk factors.Material and methods. The study included 160 patients (56 men and 104 women) with the median age of 39 [22,0;57,0] years. All patients underwent an anthropometric measurement and a study of lipid profile (total cholesterol (TC), low- and high-density lipoprotein cholesterol and triglycerides) using the CardioChek PA analyzer (USA, 2020) with subsequent calculation of lipid accumulation product (LAP), visceral adiposity index (VAI), body fat percentage (BFP), body adiposity index (BAI). Increased arterial stiffness was assessed by the CAVI level by the sphygmomanometry using the VaSera-1000 FUCUDA DENSHI system (Japan, 2010). Statistical analysis was carried out using the Jamovi program.Results. The incidence of abdominal obesity, hypertension, dyslipidemia and smoking was consistent with the general population. There were no significant relationships between CAVI and anthropometric metabolic markers (weight, body mass index, waist circumference, hip circumference, neck circumference) (p>0,05). Significant direct correlations between CAVI and the levels of TC, low-density lipoprotein cholesterol and integral metabolic indices (LAP, VAI and BFP) were revealed. The strongest correlation was obtained between CAVI and LAP, BFP. According to multivariate analysis, an independent relationship with CAVI was detected only in LAP and VAI, for which ROC analysis was performed. With LAP >39, increased arterial stiffness can be detected with a sensitivity of 75,24% and specificity of 77,68% (Area Under the Curve (AUC) 0,859, threshold =39). For VAI, a model with a high specificity of 100% but a low sensitivity of 18,2% (AUC 0,617) was obtained.Conclusion. To identify early vascular aging in young and middleaged people, in addition to traditional metabolic markers, the LAP can be used, which, with a value of >39, allows one to predict high arterial stiffness with a sensitivity of 75,24% and a specificity of 77,68%.